ZnO-nitrogen doped carbon derived from a zeolitic imidazolate framework as an efficient counter electrode in dye-sensitized solar cells. Issue 8 (27th February 2019) - Ahmed, Abdelaal S. A.; Xiang, Wanchun; Amiinu, Ibrahim Saana; Li, Ziying; Yu, Ruohan; Zhao, Xiujian
Abstract : ZnO-nitrogen doped carbon (ZnO-NC) derived ZIF-8 mixed with polystyrenesulfonate-doped poly(3, 4-ethylenedioxythiophene) (PEDOT:PSS) employed as an efficient catalyst in dye-sensitized solar cells (DSSCs). Abstract : By direct carbonization of ZIF-8 nanopowder under an inert atmosphere, ZnO-nitrogen doped carbon (ZnO-NC) materials have been prepared and added at different content values to polystyrenesulfonate-doped poly(3, 4-ethylenedioxythiophene) (PEDOT:PSS) and employed as an efficient catalyst in dye-sensitized solar cells (DSSCs). The electrochemical analysis confirms that the prepared counter electrodes display catalytic activity higher than those of PEDOT:PSS and Pt CEs for I3 − /I − and [Co(bpy)3 ] 2+/3+ redox mediators. The photovoltaic conversion efficiency of the assembled DSSC with the 7% ZnO-NC/PEDOT:PSS catalyst and an I3 − /I − based electrolyte is 8.05%. By increasing the thickness of the prepared counter electrode, the electrocatalytic activity is greatly enhanced and the total performance reaches 9.16%, which is 21.16% greater than that of the Pt-based cell (7.56%). Furthermore, ZnO-NC/PEDOT:PSS CEs are also confirmed to exhibit outstanding catalytic activity toward the [Co(bpy)3 ] 2+/3+ redox couple. The resultant conversion efficiency of the assembled DSSC with a 7% ZnO-NC/PEDOT:PSS CE is 8.12%, which is greater than that of the Pt-based cell (7.49%).